THE SUPERVISION OF TEACHING AS AN INDUCTOR OF THE STRENGTHENING IN THE CONTINUING EDUCATION OF EDUCATION PROFESSIONALS OF THE SAO PAULO STATE PUBLIC NETWORK - Campos Martins, Chelsea Maria de [UNESP]; Cedran, Paulo Cesar (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The paper aims to investigate the contribution of the teaching supervisor when analyzing the importance of its action and to what extent it provokes in education professionals a reflection on the proposal of continuing education offered by the Sao Paulo State Public Network. It is a discussion aimed at apprehending and analyzing the challenges posed to the teaching supervisor in the management of continuing education for education professionals of this public network. It is concluded that the challenges of the supervisory action in the formation of education professionals can contribute to improving the quality of education offered to students in public schools, since access to and permanence in public schools have already been guaranteed almost in its entirety and can strengthen the offer of a school with higher quality teaching.
Keywords: Teaching supervision; Continuing education; Education professionals